2016
DOI: 10.3748/wjg.v22.i7.2284
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of esophageal squamous cell carcinoma: Insights from next-generation sequencing

Abstract: Two major types of cancer occur in the esophagus: squamous cell carcinoma, which is associated with chronic smoking and alcohol consumption, and adenocarcinoma, which typically arises in gastric reflux-associated Barrett's esophagus. Although there is increasing incidence of esophageal adenocarcinoma in Western counties, esophageal squamous cell carcinoma (ESCC) accounts for most esophageal malignancies in East Asia, including China and Japan. Technological advances allowing for massively parallel, high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 78 publications
1
44
0
Order By: Relevance
“…Correlation between RKIP protein expression and clinicopathological characteristics. epigenetic alterations also play significant roles in the development of multiple cancers, including ESCC (30)(31)(32). Among various epigenetic alterations, aberrant DNA methylation (including hypomethylation of oncogenes and hypermethylation of tumor suppressor genes) is the best characterized and most crucial mechanism modulating chromatin structure and the expression levels of oncogenes or tumor suppressor genes, contributing to tumor initiation and further development (33).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between RKIP protein expression and clinicopathological characteristics. epigenetic alterations also play significant roles in the development of multiple cancers, including ESCC (30)(31)(32). Among various epigenetic alterations, aberrant DNA methylation (including hypomethylation of oncogenes and hypermethylation of tumor suppressor genes) is the best characterized and most crucial mechanism modulating chromatin structure and the expression levels of oncogenes or tumor suppressor genes, contributing to tumor initiation and further development (33).…”
Section: Discussionmentioning
confidence: 99%
“…31 A couple of studies summarized and re-analyzed the genomic data from several recent genomic studies of large cohorts of ESCC patients. 32,33 The re-analysis by Du et al identified recurrent mutations in approximately 18 genes, 15 of which had been reported previously (TP53, AJUBA, CDKN2A, KMT2D (MLL2), ZNF750, FAT1, NOTCH1, NOTCH3, PIK3CA, NFE2L2, RB1, KDM6A, FBXW7, CREBBP, and TGFBR2), with three significantly mutated novel genes (CUL3, PTEN, and DCDC1). 33 Furthermore, a recent study reported 26 significantly mutated genes, including eight novel (NAV3, TENM3, PTCH1, TGFBR2, RIPK4, PBRM1, USP8, and BAP1) and 18 that have been previously reported.…”
Section: Genomics Mutations and Deregulated Pathwaysmentioning
confidence: 90%
“…This article also discusses the epigenetic alterations in ESCC emphasizing a major challenge of understanding epigenetic mechanisms contributing to carcinogenesis . A couple of studies summarized and re‐analyzed the genomic data from several recent genomic studies of large cohorts of ESCC patients . The re‐analysis by Du et al .…”
Section: Genomics Mutations and Deregulated Pathwaysmentioning
confidence: 99%
“…Studies on the molecular mechanisms involved in metastasis of ESCC gathered knowledge that it is associated with epithelial to mesenchymal transition (EMT) and EMT‐related genes and proteins . Other studies found that TP53 gene deletion, epidermal growth factor receptor (EGFR) overexpression, integrin α7, and various other mutations and proteins are associated with distant metastasis in ESCC .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the molecular mechanisms involved in metastasis of ESCC gathered knowledge that it is associated with epithelial to mesenchymal transition (EMT) and EMT-related genes and proteins. [25][26][27] Other studies found that TP53 gene deletion, epidermal growth factor receptor (EGFR) overexpression, integrin 7, and various other mutations and proteins are associated with distant metastasis in ESCC. [28][29][30] However, it is yet unknown how the level of expression of these genes and proteins differs between the initially metastatic and recurrent/progressed ESCC after curative treatment, and how they function in each disease group.…”
Section: Discussionmentioning
confidence: 99%